Forming a children's monologue discourse: use of anaphoric means in spontaneous children's speech - Aleksandra A. Aisanova; Aleksandra S. Morozova (Sovremennye Issledovaniâ Socialʹnyh Problem)
Background. The article examines the features of the use of anaphoric means in the spontaneous oral speech of preschool children. Traditionally, children's speech is studied from the point of view of occasional formations, and the construction of children's discourse is studied to a much lesser extent. At the same time, in modern linguistics, various features of the structuring of children's monological speech remain insufficiently studied, related, in particular, to the formation of a repertoire of anaphoric means and the specifics of their use. The study of this issue will help expand the understanding of both children's speech and its features, as well as the universal mechanisms of generating oral unprepared discourse.